Nelson textbook of pediatrics - Kliegman, Robert; St. Geme, Joseph W.; Blum, Nathan J.; Schuh, Abigail M.; Tasker, Robert C. (Robert Charles), 1958-; Mack, Cara L.; Wilson, Karen M.; Deardorff, Matthew A (Philadelphia, PA : Elsevier, 2025)
Covering every aspect of general pediatric practice, as well as details for many pediatric subspecialists, Nelson Textbook of Pediatrics, 22nd Edition, brings you fully up to date with everything from rapidly changing diagnostic and treatment protocols to new technologies to the wide range of biologic, psychologic, and social problems faced by children today. Edited and written by experts and prominent members of the pediatric medical community, this comprehensive two-volume reference covers both the science and art of pediatric practice. It remains the reference of choice among pediatricians, pediatric residents, and others involved in the care of young patients, delivering the information you need in a concise, easy-to-use format for everyday reference and study
The field of pediatrics -- Growth, development, and behavior -- Behavioral and psychiatric disorders -- Learning and developmental disorders -- Nutrition -- Fluid and electrolyte disorders -- Emergency medicine, critical care, and anesthesia -- Human genetics -- Metabolic disorders -- The fetus and the neonatal infant -- Adolescent medicine -- Allergic disorders -- Rheumatic diseases of childhood (Connective tissue disease, collagen vascular diseases) -- Cancer and benign tumors -- Urologic disorders in infants and children -- Gynecologic problems of childhood -- The nervous system -- Neuromuscular disorders -- Disorders of the eye -- The ear -- The skin -- Rehabilitation medicine -- Environmental health -- Laboratory medicine
Includes bibliographical references
Keywords: Pediatrics -- Textbooks; Pediatrics; Pediatrics(DNLM)D010372